INFORMATION FIELDS OF THE FUTURE’S DESIGNING - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2025)
The question of socio-cultural and political-economic programming of transformations naturally becomes more acute at the turning point of eras, when the foundation of a new reality is being formed, when long-term orbits of subsequent changes are being determined [1-5]. At the moment of active competition between people and models, everything is not predetermined, everything is shaky and fluctuates. And it is not at all necessary that the optimal path will be chosen, as well as the stages and the best pace of movement.